An assessment of the carbon footprint of tropical hardwood sawn timber production - Ratnasingam, Jegatheswaran; Ramasamy, Geetha; Toong, Weiching; Senin, Abdul Latib; Kusno, Mohd Ashadie; Muttiah, Neelakandan (North Carolina State University, 2015)
The demand for sawn timber throughout the world is steady, as wood is one of the most important raw materials available to mankind. Yet, the production of sawn timber through sawmilling activities causes environmental issues and is perceived to have a potential effect on global warming. Studies on this aspect is very limited, especially for tropical hardwoods. The intention for this study was to evaluate the carbon footprint of manufacturing sawn timber from round wood using a gate-to-gate life cycle approach. The functional unit used was 1 m3 of rough green sawn timber. Primary data on yield and energy consumption during the sawmilling process were collected on a monthly basis throughout 2013. Greenhouse gas emissions, which include CO2, CH4, and N2O, were determined using emission factors. The carbon footprint was then calculated on the basis of the equivalency factor, described as CO2-eq. The carbon footprint assessment shows a result of 499 kg CO2-eq/m3 and 696 kg CO2-eq/m3 for Light Red Meranti and Dark Red Meranti sawn timber, respectively. The results showed that there were no significant differences in the carbon footprint of Light Red Meranti and Dark Red Meranti sawn timber production.